The Utilization of Sediment Mud In Water Channel And Urban Organic Compost Waste For Sunflower (Helianthus Anuus L.Var. Early Russian) Cultivation - Dwi Haryanta; Fungki Sri Rejeki (Faculty of Agriculture, Merdeka University Surabaya, 2021)
This research aims to analyze the response of sunflower plants which planted in sediment mud from water channel media and urban organic compost waste. This research conducted by applying T1: river sediment mud, T2: pond sediment mud, T3: highway water channel sediment mud, T4: sediment mud of residential sewerage, and T5: garden soil as a comparison factor. While the treatment of second factor are amount (dose) of urban organic compost waste, namely B0: 0% compost as control, B1: 10%, B2: 20%, and B3: 30% compost. The experiment using a randomized block design is repeated three times. The experimental unit is a plant in a 50 cm diameter polybag that filled by 40 cm mud as media, filled with media as high as 40 cm. There are 60 sunflower plants for experiment. The results shows that there is no interaction between the treatment factors of sediment mud in water channel with the provision of municipal compost waste for all research variables. The treatment of sediment mud in water channel including the use of garden soil as a comparison factor is not significantly affect all research variables. As the result, sediment mud in water channel could be used as a substitute for garden soil. The treatment of urban organic compost waste has a significant influence on growth variables, they are increasing plant height, leaf number, leaf size, stem diameter, flower diameter, and shortening flowering life (7 days). The treatment of urban organic compost waste does not influence toward the production variables, which include plant height, flower bunch weight, seed weight, and seed yield toward flower bunches.